Effect of session order in combined aerobic and resistance training on glycemic control in older adults with type 2 diabetes: a crossover study - Renato Ferreira Corrêa; João Guilherme Vieira; Marcelo Ricardo Dias (Revista Brasileira de Atividade Física e Saúde)
The session order of aerobic and resistance training seems to be important for glycemic behavior, as when performed in isolation they help to reduce glycosylated hemoglobin. The purpose of the present study was to compare the acute effect of aerobic and resistance training session orders on glycemia levels of older adults with type 2 diabetes mellitus. A counterbalanced crossover design was used in this study. Eighteen older adults with type 2 diabetes, 13 men and 5 women, non-insulin and beta-blocker dependents, were recruited. All participants performed two training sessions in different orders: aerobic + resistance (AER) and resistance + aerobic (RES). There was a seven-day interval between sessions. In the AER session, a significant (p < 0.001) decrease in blood glucose was observed between training (Mid moment: p < 0.001) and after each session (Post moment: p = 0.003) compared to the baseline (Pre moment). In the RES session, no difference (p = 0.731) was found at the Mid moment in relation to the Pre moment, but a significant (p < 0.001) decrease in blood glucose was observed in the Post moment. A comparison of the different training sessions showed a significant difference (p = 0.012) at the Mid moment, whereas the blood glucose showed a sharper reduction the AER session. In conclusion, we observed that combined training, regardless of the order, was effective for acute glycemic behavior in older people with type 2 diabetes, and aerobic training was the main factor responsible for the reduction blood glucose.